Analysis of the Influence of Leadership Style, Work Environment, and Organizational Culture on Employee Performance at the Lowokwaru District Office, Malang City - Emilius Janggur; Cakti Indra Gunawan; Fendiyatmi Kusufa (International Journal of Management and Business, 2026)
This study aims to determine the influence of leadership style, work environment, and organizational culture on employee performance productivity at the Lowokwaru District Office, Malang City. The background of this study is based on the importance of increasing employee performance productivity in supporting the quality of public services at the sub-district level. Leadership factors, work environment conditions, and organizational culture are suspected to be important elements that influence the high and low employee work productivity. This study employs a quantitative approach using a survey method. The population consists of all 30 employees at the Lowokwaru District Office in Malang City, therefore a saturated sampling technique is applied. Data were collected through questionnaires and analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and coefficients of determination (R²). The results of the study indicate that partially leadership style, work environment, and organizational culture have a positive and significant effect on employee performance productivity. Leadership style is the most dominant variable influencing employee performance productivity. Simultaneously, the three independent variables also have a significant effect on employee performance productivity with a coefficient of determination (R²) of 0.588. This means that 58.8% of employee performance productivity can be explained by leadership style, work environment, and organizational culture, while the remaining 41.2% is influenced by other factors outside the research. Based on the research results, it can be concluded that increasing employee performance productivity at the Lowokwaru District Office, Malang City requires the support of an effective leadership style, a conducive work environment, and a strong and positive organizational culture